Labuan, Malaysia : Assessment of the Supervision and Regulation of the Financial Sector-Review of Financial Sector Regulation and Supervision. (IMF Staff Country Reports; Country Report, 2004)
This Review of Financial Sector Regulation and Supervision in Labuan, Malaysia, highlights the supervisory and antimoney laundering frameworks. Labuan, an offshore financial center located in Malaysia, has all the essential elements for a suitable framework for financial supervision. Nonperforming loans are relatively high in the banking sector, and demand for credit has been soft. Securities and capital market activities in Labuan are still embryonic, and the supervisory regime for this sector will need to be fleshed out as business develops.